Current Blood Salvage Technologies during Pelvic Repair - Z. G. Marutyan; Yu. V Nikiforov; A. B. Kazantsev; A. A. Ter-Grigoryan (Общая реаниматология)
The introduction of current technologies into traumatology and orthopedics, anesthesiology and reanimatology and the accumulation of practical experience extend the feasibilities of highly skilled care to patients with pelvic fractures. Reconstructive operations that are one of the most complex and highly traumatic types in orthopedics are accompanied by massive intra- and postoperative blood loss. Its level is as high as 800 to 6000 ml. Until recently, blood loss has been compensated for with allogenic blood preparations. However, the complications resulting from the use of donor blood are universally known. This has caused indications for the use of blood preparations to be revised and a number of alternatives associated with the use of a patient’s blood to be developed. This alternative is current blood salvage technologies. Key words: autodonation, acute hypervolemic hemodilution, instrumental washed autoerythrocyte reinfusion, drainage blood reinfusion.